Computational Methods and Experimental Measurements XVI 2013
DOI: 10.2495/cmem130381
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of planning strategies for track allocation at marshalling yards

Abstract: Planning the operational procedures in a railway marshalling yard is a complex problem. When a train arrives at a marshalling yard, it is uncoupled at an arrival yard and then its cars are rolled to a classification yard. All cars should eventually be rolled to the classification track that has been assigned to the train they're supposed to depart with. However, there is normally not enough capacity to compound all trains at once. In Sweden, cars arriving before a track has been assigned to their train can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…FIGURE 14 Benefit ratios corresponding to the optimal minimum numbers of wagons under different wagon flow intensities Figure 14 shows the relationship between the benefit ratios and optimal minimum number of wagons:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIGURE 14 Benefit ratios corresponding to the optimal minimum numbers of wagons under different wagon flow intensities Figure 14 shows the relationship between the benefit ratios and optimal minimum number of wagons:…”
Section: Discussionmentioning
confidence: 99%
“…Marinov and Viegas [12,13] used SIMUL'8 to establish a simulation model for analysing and evaluating the operation of a flat-shunted yard. Bohlin et al [14] compared different track allocation strategies in the accumulation process of wagons through a simulation method, namely the 'first come first served' strategy and the departure time limit strategy, and found that the departure time limit strategy performed better. Khadilkar and Sinha [15] simulated operation processes such as arrival, breaking-up and marshalling of reorganization trains in the marshalling yard, and obtained the operation scheme with the shortest waiting time of wagons.…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing and summarizing simulation tools used in the past and the current state-of-the-art in railroad terminal simulation models, the authors identified three major types of simulation tools: general coding languages, general-purpose simulation software, and custom commercial simulations (Tables 1–3). General coding languages (Table 1) are the most common tools, with researchers converting yard operation to a Monte Carlo process ( 31 , 32 ), mathematical functions ( 32 – 35 ), a queuing model ( 36 ), or a discrete-event list ( 37 , 38 ) featuring computerized simulation instead of manual calculation. Despite the flexibility and ease of building the model, common limitations of these general coding languages are a lack of detailed operating and geometric features and an inability to reflect the specific traffic flow movements of the yard operation.…”
Section: Previous Researchmentioning
confidence: 99%
“…58,59 SIMUL8 was used for discrete-event simulation of the largest flat-switching yard in Portugal 60 while a MATLAB model simulated the Hallsberg hump classification yard in Sweden. 52 Hump classification yards have also been simulated in the general-purpose AnyLogic simulation environment. 18,30 CSX and Optym partnered to develop the web-based Hump Yard Simulation System (HYSS) now known as YardSYM and consisting of a discrete-event simulation model for analysis of hump classification yards.…”
Section: Previous Researchmentioning
confidence: 99%
“…18 Initial simulation models were based on computerized versions of the yard charts used in manual simulation. [52][53][54][55][56][57] Among these early efforts, Reinschmidt examined the influence of various infrastructure and resource parameters on hump yard capacity through singlevariable experiments and analysis. 29 This paper specifically examines the interaction between volume, number of blocks and yard dwell time.…”
Section: Previous Researchmentioning
confidence: 99%